Bridging entrepreneurial cognition research and entrepreneurship education: what and how - Santos, S. C.; Silva, S.A.; Neumeyer, X.; Neumeyer, X.; Caetano, António (Annals of Entrepreneurship Education and Pedagogy - 2016, 2016)
This chapter contributes to the debate about what and how entrepreneurship should be taught. First, cognitive entrepreneurship education is introduced as the answer to the what question. Cognitive entrepreneurship education emerges from where entrepreneurial cognition, evidence-based teaching and entrepreneurship education intersect. On the basis of this intersection, cognitive entrepreneurship education is defined as those activities which, based on available evidence, aim to foster the knowledge structures that individuals use to make assessments, judgments or decisions involving opportunity evaluation, and venture creation and growth. Second, it is proposed that experiential learning is the most adequate method for how entrepreneurship should be taught, as it is more effective for learning and changing knowledge structures and reasoning processes. Using the experiential learning model of Kolb (1984) the authors suggest that five subjects of cognitive entrepreneurship education can be delivered using specific learning styles. These two building blocks constitute the foundations for developing students’ mindsets and awareness of entrepreneurship.